Comparison and Characterization of Oxidation Resistance and Carbohydrate Content in Cd-Tolerant and -Sensitive Kentucky Bluegrass under Cd Stress - Yong Wang (MDPI AG, 2021)
Kentucky bluegrass (Poa pratensis L.), a turf grass species that is hypertolerant of cadmium (Cd), is a potential phytoremediation material for soil polluted with Cd. However, the mechanism of Cd phytotoxicity in Kentucky bluegrass is unclear. Here, we compared the phenotype, induction of oxidative stress, and structural and non-structural carbohydrate contents between a Cd-tolerant genotype (‘Midnight’, M) and Cd-sensitive genotype (‘Rugby’, R). The results showed that both genotypes accumulated more Cd in the roots, whereas the R genotype distributed more Cd into the leaves compared with the M genotype. In both genotypes, Cd inhibited the length and fresh weight of the leaves and roots; increased the peroxidase (POD) activity but inhibited ascorbate peroxidase (APX) and catalase (CAT) activity; and increased the superoxide radical (O2−), hydrogen peroxide (H2O2), and malondialdehyde (MDA) contents. However, the M genotype exhibited lower root length inhibition, and the H2O2 and MDA contents confirmed that the M genotype had increased Cd accumulation and resistance, while the R genotype exhibited a better distribution of Cd. Moreover, Cd stress significantly increased the soluble sugar, trehalose, and sucrose contents of both genotypes. Pectin, lignin, and cellulose were significantly increased to prevent the entry of Cd into the roots. The Cd-induced growth inhibition and physiological responses in Kentucky bluegrass were preliminarily explored herein, with the chelation of pectin, lignification, and antioxidant response being possible contributors to Cd detoxification in Kentucky bluegrass. In addition, the Cd-induced increase in trehalose, sucrose, and soluble sugar contents might play a pivotal role in the defense against Cd stress in Kentucky bluegrass.